2013
DOI: 10.1159/000354776
|View full text |Cite
|
Sign up to set email alerts
|

The Inside-Out Amyloid Hypothesis and Synapse Pathology in Alzheimer's Disease

Abstract: Cumulative evidence in brains and cultured neurons of Alzheimer's disease (AD) transgenic mouse models, as well as in human postmortem AD brains, highlights that age-related increases in β-amyloid peptide (Aβ), particularly in endosomes near synapses, are involved in early synapse dysfunction. Our immunoelectron microscopy and high-resolution immunofluorescence microscopy studies show that this early subcellular Aβ accumulation leads to progressive Aβ aggregation and pathology, particularly within dystrophic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…However, this might be cell-specific, as Cha et al [24] reported mitochondrial alterations after the endocytosis of extracellular Aβ42. Indeed, the idea of intracellular Aβ toxicity has strengthened in recent years [5457]. In particular, Aβ accumulation in mitochondria has been reported in several studies [58] potentially deriving from an Aβ release in mitochondria-associated membranes [59] or even in mitochondria [60].…”
Section: Discussionmentioning
confidence: 99%
“…However, this might be cell-specific, as Cha et al [24] reported mitochondrial alterations after the endocytosis of extracellular Aβ42. Indeed, the idea of intracellular Aβ toxicity has strengthened in recent years [5457]. In particular, Aβ accumulation in mitochondria has been reported in several studies [58] potentially deriving from an Aβ release in mitochondria-associated membranes [59] or even in mitochondria [60].…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of A␤ staining in hippocampus and prefrontal cortex observed here does not indicate an advanced stage of neurodegeneration commonly associated with the presence of amyloid plaques but intraneuronal accumulation of A␤ or, more likely, its full-length precursor protein, considering the morphological pattern of staining. Early intraneuronal accumulation of A␤ in neurons that are particularly vulnerable in AD were observed in AD brains, as well as Down's syndrome and numerous transgenic mouse models of AD (57). This "preplaque" accumulation takes place in intraneuronal endosomal vesicles, reportedly located in cell soma and, at higher extent, distal neurites and synapses (58,59).…”
Section: Rage Mediates Neurodegeneration In Sepsismentioning
confidence: 99%
“…These may be the consequence of intraneuronal APP accumulation or the accumulation of BACE1 derived cleavage products rather than due to soluble amyloid species of any type or location [75]. Recently, knock-in animal models expressing physiological quantities of mutant APP have been generated to help differentiate between synaptic and cognitive effects caused by overexpression and those by mutation of APP.…”
Section: Intraneuronal Amyloid Betamentioning
confidence: 99%